Psychoeducation for bipolar disorder and risk of recurrence and hospitalization – a within-individual analysis using registry data. Issue 6 (6th April 2020) - Joas, Erik; Bäckman, Kristoffer; Karanti, Alina; Sparding, Timea; Colom, Francesc; Pålsson, Erik; Landén, Mikael
Abstract: Background: The efficacy of psychoeducation for bipolar disorder has been demonstrated in clinical trials, but it is not known if the results translate into effectiveness in routine clinical practice. The aim was to determine the effectiveness of psychoeducation for bipolar disorder in a routine clinical setting. Method: We identified 2819 patients with at least three registrations in the Swedish Quality Assurance Register for Bipolar Disorder. Among those, 402 had not been exposed to psychoeducation at the first visit, but received psychoeducation during any of the following registrations. Using within-individual analyses, the risk of recurrence after having received psychoeducation was compared with the risk prior to psychoeducation. Results: In adjusted within-individuals comparisons, periods after psychoeducation was associated with decreased risks of any recurrence [odds ratio (OR) 0.57, 95% CI 0.42–0.78], (hypo-)manic or mixed episodes (OR 0.54, 95% CI 0.39–0.76), depressive episodes (OR 0.63, 95% CI 0.47–0.86), and inpatient care (OR 0.54, 95% CI 0.33–0.86) relative to periods prior to psychoeducation. There was no association with rates of involuntary sectioning or suicide attempts. Conclusions: The results suggest that psychoeducation for bipolar disorder reduces the risk of mood episodes and inpatient care also when implemented in routine clinical practice.